Relationships among critical success factors of knowledge management and organizational ‎performance - Naghavi, M.; Amir Hossein, D.; Hossein, N. (2013)
The main objective of this study is to find relationships among critical success factors of ‎knowledge management (KM) include; organizational factors and KM processes with ‎organizational performance. The research proposes that KM in the public sector is still in its ‎infancy and has a long way to go in the KM journey. However, the study has identified a certain ‎number of factors that are essential to the success of the KM initiative and program in the public ‎sector. The study also explain current situation in terms of KM activities in the public sector in ‎Iran and sustain the discussion about KM processes in the public sector. The result of this ‎investigation could have significant implications for KM programs in public sector organizations ‎in Iran. The paper describes and develops a framework of KM process in the public sector as well ‎as recommendations to practitioners about planning and implementing KM programs and ‎initiatives.‎